W.E.B Du Boise - Stafford, Mark; Edited BY Huggins, Nathan Irvin (New York Chelsea House, 1989)
Examines the life of the black scholar and leader who devoted himself to gaining equality for his people.
Include Illustration, Indexes
Introductory essay by Coretta Scott King
Keywords: United States -- Du Bois, W. E. B. (William Edward Burghardt), 1868-1963 -- National Association for the Advancement of Colored People